Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berbantuan Geogebra dalam Meningkatkan Kemampuan Berpikir Kreatif Matematis Siswa - Malail, Baiq; Muhammad Turmuzi; Junaidi (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This research is motivated by the low level of students’ mathematical creative thinking ability, which is caused by low student engagement during the learning process and a lack of understanding of mathematical concepts. This study aims to determine the effect of the GeoGebra-assisted Problem-Based Learning (PBL) model on improving the mathematical creative thinking ability of students. This research employs a quantitative approach with a quasi-experimental method. The subjects of this study were class VIII A as the experimental group and class VIII B as the kontrol group. Data collection techniques included a post-test and an observation sheet to measure the implementation of the learning process. Based on the research findings and discussion, it can be concluded that the implementation of the GeoGebra-assisted Problem-Based Learning (PBL) model can enhance the mathematical creative thinking ability of students. This is evident from the significant difference in the average post-test scores between the experimental and kontrol classes.